2013
DOI: 10.5539/ijps.v5n1p128
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Antecedents of Organizational Citizenship Behaviour: Case of Saudi Arabia

Abstract: Organizational Citizenship Behaviour (OCB) has been signified as one of the antecedents of organizational effectiveness. OCB is widely studied over the years in the US but has received relatively inadequate attention in other Asian contexts. This study explored and examined number of predictors of OCB in the Arabic-speaking context (Saudi Arabia in Gulf). The data was drawn from 275 employees of both private and public banking sectors. Predictors of OCB examined are Job Satisfaction and Organizational Commitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…Employees are satisfied with their work have a greater opportunity to speak positively about the organization, help colleagues, and perform beyond the normal performance. Research by Organ and Konovsky (1989) [47], Yoon and Suh (2003) [76], Gonzales and Garazo (2006) [20], Zeinabadi (2010) [79], Rasheed, et al (2013) [53], Zeinabadi and Salehi (2011) [80] and Salehi and Gholtash (2011) [56] found that job satisfaction significantly effects OCB. Based on those results, the fifth research hypothesis can be stated as follows:…”
Section: Theoretical Framework and Researchmentioning
confidence: 99%
“…Employees are satisfied with their work have a greater opportunity to speak positively about the organization, help colleagues, and perform beyond the normal performance. Research by Organ and Konovsky (1989) [47], Yoon and Suh (2003) [76], Gonzales and Garazo (2006) [20], Zeinabadi (2010) [79], Rasheed, et al (2013) [53], Zeinabadi and Salehi (2011) [80] and Salehi and Gholtash (2011) [56] found that job satisfaction significantly effects OCB. Based on those results, the fifth research hypothesis can be stated as follows:…”
Section: Theoretical Framework and Researchmentioning
confidence: 99%
“…This is in accordance with Bernardin and Beatty (1984), who suggested that dissatisfaction with feedback can make the feedback ineffective in the improvement of performance. Conversely, many researchers have found a positive association between satisfaction with feedback and motivation that improves performance (e.g., Gosselin, Werner, & Halle, 1997;Rasheed, Jehanzeb, & Rasheed, 2013;Russell & Goode, 1988). Accordingly, research on feedback (e.g., Brett & Atwater, 2001;Mishra & Farooqi, 2013) has established that degree of feedback acceptance and individual intention to use feedback for performance improvement were significantly linked.…”
Section: Satisfaction With Feedbackmentioning
confidence: 99%
“…The relationship between EE and the following concepts: job burnout (Babcock-Roberson and Strickland, 2010; Gonzalez-Roma, Schaufeli and Bakker, 2006), job involvement (Mauno, Kinnunen and Ruokolainen, 2007), job satisfaction (Ariani, 2013), self management (Breevaart, Bakker and Demerouti, 2014;Murphy and Ensher, 2001;Raabe, Frese and Beehr, 2007) and organizational success (Avery et al, 2007;Kaliannan and Adjovu, 2015). The different antecedents (predictors) of EE such as: job fit (Resick, Baltes and Shantz, 2007;Shuck, Reio and Rocco 2011), rewards and recognition (Sahoo and Mishra, 2012), perceived organizational/supervisory support (Bates, 2004;Rasheed, Jehanzeb, and Rasheed, 2013;Rhoades and Eisenberger, 2002), organizational justice (Colquitt, 2001), job characteristics (May, Gilson and Harter, 2004), organizational commitment (Ariani, 2013;Soieb, Othman and D'Silva, 2013) and job satisfaction (Abraham, 2012). The different consequences of EE such as: turnover intent (Harter, Schmidt andHayes, 2002, Saks, 2006) and discretionary behaviours (Lloyd, 2008;Macey and Schneider, 2008).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%